Clinical spectrum and outcomes of the 2019-2020 pediatric diphtheria outbreak in Yemen - Bawazir, Omar Abdul-Rahman Bawazir; Binkroom, Noor Abdulaziz; Binghouth, Abdulla Salem (Paediatrica Indonesiana, 2024)
Background Diphtheria is an acute bacterial infectious disease characterized by serious morbidity and mortality. Outbreaks continue to occur in developing countries despite national vaccination programs. Vaccination, early recognition the disease, and adequate intervention are needed to avoid devastating outcomes. Objective To describe the clinical spectrum of childhood diphtheria and its association to outcomes during the 2019-2020 diphtheria outberak in Yemen. Methods This was a retrospective study to assess the demographic, clinical features, and outcomes of paediatric respiratory diphtheria in patients with diphtheria during the outbreak from September 2019 until May 2020 admitted at Mukalla Maternity and Children Hospital. We used SPSS 22 version for data analysis. Results There were 34 culture-confirmed diphtheria cases included in this study, their age ranged from 13 months to 15 years old. Most of the cases (76.5%) happened to children at more than 5 years old. There was no gender difference. Of these 34-positive diphtheria, 79.4% from Hadramout and 17.6% from Shabwa governorate. Most of the cases (35.3%) were admitted in December. More than half of the patients (52.9%) were unimmunized. Fever, sore throat, and enlarged tonsils were presented in all patients, dysphagia (82.4 %), pseudomembrane (91.7%), bull neck (52.9%), and stridor (8.8%) were also found in some patients. Complications included acute renal failure (20.6%), disseminated intravascular coagulation (DIC), shock (17.6%), and myocarditis (8.8%). Significant poor outcome (P< 0.05) was associated with bull neck, myocarditis, acute renal failure, DIC, and shock. The case fatality rate (CFR) was 20.6%. Conclusion Fever, sore throat, tonsillitis, pseudomembrane, and bull neck are high index suspicion of diphtheria and anticipation of ominous outcome. The shifting of occurrence of diphtheria to older age group indicates the need for booster(s) diphtheria toxoid vaccine in addition to improving and strengthening the current immunization program.